2005
DOI: 10.1016/j.ccr.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with chemotherapy crossresistance and treatment response in childhood acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) can be cured with combination chemotherapy in over 75% of children, but the cause of treatment failure in the remaining patients is unknown. We determined the sensitivity of ALL cells to individual antileukemic agents in 441 patients and used a genome-wide approach to identify 45 genes differentially expressed in ALL exhibiting crossresistance to prednisolone, vincristine, asparaginase, and daunorubicin. We also identified a distinct phenotype of discordant resistance to aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 39 publications
(9 reference statements)
2
91
0
1
Order By: Relevance
“…Whereas gene expression-profiling studies in the acute leukemias have identified gene expression signatures associated with recurrent cytogenetic abnormalities 8,25,26 and in vitro drug responsiveness, [9][10][11]15 fewer studies have reported and validated gene expression classifiers predictive of survival. 13,14 In this study, gene expression classifiers predictive of RFS and end-induction MRD were derived from the gene expression profiles obtained in the pretreatment samples of 207 children with B-precursor high-risk ALL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas gene expression-profiling studies in the acute leukemias have identified gene expression signatures associated with recurrent cytogenetic abnormalities 8,25,26 and in vitro drug responsiveness, [9][10][11]15 fewer studies have reported and validated gene expression classifiers predictive of survival. 13,14 In this study, gene expression classifiers predictive of RFS and end-induction MRD were derived from the gene expression profiles obtained in the pretreatment samples of 207 children with B-precursor high-risk ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gene expression profiling and other comprehensive genomic technologies, such as assessment of genome copy number abnormalities or DNA sequencing, have the potential to resolve the underlying genetic heterogeneity of this form of ALL and to capture genetic differences that impact treatment response that can be exploited for improved risk classification and the identification of novel therapeutic targets. [8][9][10][11][12][13][14][15] From the gene expression profiles obtained in the pretreatment leukemic cells of 207 uniformly treated children with high-risk ALL, we used supervised learning algorithms and extensive cross-validation techniques to build a 42-probe-set (38-gene) expression classifier predictive of RFS. In multivariate analysis, the best predictive model for RFS was this gene expression classifier combined with either flow cytometric measures of MRD determined at the end of induction therapy (day 29), or, a 23-probe-set (21-gene) molecular classifier derived from pretreatment samples that could predict levels of end-induction flow MRD at initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified 45 genes differentially expressed between resistant and sensitive ALL samples whose expression pattern was significantly related to treatment response (28). The 45 genes were involved in the regulation of transcription, cellular transport and cell cycle maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Briefly, gene expression profiling data from previous studies [7][8][9][10]19,20 comparing therapeutic response with various reagents in ALL patients were pooled and normalized. Relative expression levels were calculated, and associated with outcomes by analysis of variance (ANOVA).…”
Section: Selection Of Genes For Transcript Profilingmentioning
confidence: 99%
“…[6][7][8][9][10] Except for the common finding that most Ph þ ALL cases have deletions on chromosome 7p spanning the IKZF1 gene, 11 the gene expression profiling results have varied considerably in different studies, and have been of limited clinical utility.…”
mentioning
confidence: 99%